2021
DOI: 10.9755/ejfa.2021.v33.i8.2744
|View full text |Cite
|
Sign up to set email alerts
|

Apricot Production Forecast of the Leading Countries in The Period of 2018-2025.

Abstract: The aim of this study is to estimate apricot production quantities in 2018-2025 periods by using 1961-2017 data of the leading countries in apricot production in the world. 57-year data were obtained from FAOSTAT and analyzed with the help of the SAS 9.4 statistics program. In order to determine these predictions, ARIMA models have been used. In cases where the data is not stationary, the one-year delay was made and the most suitable ARIMA model was chosen according to AIC, BIC, SSE, MSE, MPE criteria. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These compounds may be necessary for human health [2,3]. The leading countries in terms of the production of apricot, as estimated for 2018-2025, are Turkey, Uzbekistan, Algeria, and Italy [4]. Apricot seeds have great industrial potential.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds may be necessary for human health [2,3]. The leading countries in terms of the production of apricot, as estimated for 2018-2025, are Turkey, Uzbekistan, Algeria, and Italy [4]. Apricot seeds have great industrial potential.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results were compared with the 2nd and 3rd order regression models obtained using the Matlab curve fitting toolbox [11]. Previously, estimates of annual apricot production for Turkey were presented using various time series analyses in some previous studies [12], [13]. In this study, an application of the PID-based optimizer system [10] was demonstrated for the polynomial modelling of the annual apricot production data from Malatya region.…”
Section: Introductionmentioning
confidence: 99%